2015
DOI: 10.1002/app.42582
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and mechanical properties of liquid silicone rubber composites filled with functionalized graphene oxide

Abstract: To improve the thermal and mechanical properties of liquid silicone rubber (LSR) for application, the graphene oxide (GO) was proposed to reinforce the LSR. The GO was functionalized with triethoxyvinylsilane (TEVS) by dehydration reaction to improve the dispersion and compatibility in the matrix. The structure of the functionalized graphene oxide (TEVS-GO) was evaluated by Thermogravimetric analysis (TGA), Fourier transform infrared (FTIR) spectra, X-ray diffraction (XRD), and energy dispersive Xray spectrosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…1(b) is the magnified pattern of GO. A narrow and sharp diffraction of graphite can be observed at 2h = 26.5°, corresponding to the characteristic peak of the C (0 0 2) plane with a D-spacing of 3.36 Å [25]. After oxidation treatment, the diffraction peak of GO shifts to 2h = 10.4°, indicating that the interlayer space increase to 8.50 Å.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…1(b) is the magnified pattern of GO. A narrow and sharp diffraction of graphite can be observed at 2h = 26.5°, corresponding to the characteristic peak of the C (0 0 2) plane with a D-spacing of 3.36 Å [25]. After oxidation treatment, the diffraction peak of GO shifts to 2h = 10.4°, indicating that the interlayer space increase to 8.50 Å.…”
Section: Resultsmentioning
confidence: 94%
“…Zhang et al [32] added 1 wt% GO into the PVDF/CNT composite, the enhancement in thermal conductivity is very obvious compared with the PVDF/CNT composite at the same CNT content. Zhao et al [25] fabricated liquid silicone rubber (LSR) composite filled with 0.3 wt% functionalized GO, the research result revealed a double increase in thermal conductivity compared with pure LSR.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Covalent and non‐covalent surface functionalizations of GO are two effective methods to improve interfacial interaction between GO and non‐polar rubbers. Covalent functionalization approach includes the reaction of coupling agents and in situ polymerization . However, this process could cause undesired permanent structure changes of GO, and it may usually be conducted in organic solvents, which would not be environmental friendly .…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, EG can be compacted into porous graphite foams under mechanical pressure without external binder because of its self‐aggregation . Finally, the compatibility between graphite and polymer is good which can be considered as the precondition for preparing EG/polymer composites . Consequently, interpenetrating networks structured composites with high thermal conductivity and high flexibility may be obtained by composing EG with PDMS.…”
Section: Introductionmentioning
confidence: 99%